Interactive Intellectual Environment as a Digital Technology of Continuous Education - Ksenia L. Polupan (Высшее образование в России)
The article presents the experience of developing technology that ensures effective digital quality control of continuous education, development of intellectual abilities and professional competencies both of students and teachers. A description of the substantive changes in control, self-development and activity processes is given. The developed technology makes it possible to completely change the control of educational and research activities not only of a student, but also of a teacher, providing an opportunity for personal design of the educational route. In the context of presence of all the subjects of the educational process in the environment, the scheme for obtaining new knowledge is fundamentally changing; this is achieved by joint actions, since the basis of an interactive intellectual environment is an interaction, a constant exchange of information, opinions, decisions, experience. Such environment has a developing character; it promotes the formation of project and heuristic skills as well as skills associated with finding and implementing non-standard solutions in professional activities. Continuous feedback distinguished by an individual approach and a high differentiation of education by means of providing each student with a personal teacher, tutor, whose role is fulfilled by a computer.